Invasion dynamics of a non-indigenous bivalve clam; Venerupis aurea (Gmelin, 1791), in Lake Qarun, Egypt. - Hashem, Kandeel (JOURNAL OF ADVANCES IN BIOLOGY, 2017)
The invasive clam Venerupis aurea is native to the Mediterranean Sea. The species has now become established in Lake Qarun, Egypt. This is the first record of the establishment of this clam in the Lake. The histograms of the length-frequency distribution indicated multiple consecutive cohorts and the species is able to establish self-sustaining population. Total weight increased relatively slower than shell length in summer. Isometric growth pattern was recorded in other seasons. Negative allometric growth pattern during summer may explain spawning. The female to male ratio is 1: 0.87. Sexual maturity is attained at 11.8 mm shell length in summer and 16.6 mm shell length in winter. Histological studies revealed two different stages in both male and female clams namely, immature and developing. The results from these preliminary studies have indicated that V. aurea is able to reproduce and survive in Lake Qarun and has an important impact in the local community of the Lake.